1. First, we can use the multiplication property of equalities, ie. if A = B then A*C = B*C. In the context of our problem, A would be (-3/14)b and B would be 2/7. We want to get rid of the denominators on both fractions, thus we should multiply them by 14 (C). Thus:
(-3/14)b*14 = (2/7)*14
-3b = 4
2. Now we can use the division property of equalities, ie. if A = B, then A/C = B/C. Here, A would be -3b and B would be 4. Since we want to get b by itself, we should divide both sides of the equation by -3. Thus:
-3b/-3 = 4/-3
b = -4/3 (Note that a negative number divided by a negative number is positive)